2017
DOI: 10.3389/fmars.2017.00157
|View full text |Cite
|
Sign up to set email alerts
|

Local Ecological Knowledge Indicates Temporal Trends of Benthic Invertebrates Species of the Adriatic Sea

Abstract: In the Adriatic Sea, shifts in benthic community structure have been attributed to multiple stressors, from the effects of climate change to the impacts of commercial fishing. Some fishing practices, such as bottom trawling, have caused a widespread decline in exploited fish stocks. Bottom trawling is also expected to have negative impacts on benthic habitats, usually structured by and hosting a large array of invertebrate species, which provide important ecological services to fish and commercial invertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…To achieve this, the use of standardized and cost-effective procedures is needed to underpin a large-scale observation strategy that can accommodate countries across a range of baseline knowledge levels and capabilities (Bélisle, Asselin, LeBlanc, & Gauthier, 2018;Latombe et al, 2017). Yet, accessing this expert knowledge (hereafter referred as local ecological knowledge or LEK) is offering new opportunities to Mediterranean research Azzurro, Moschella, & Maynou, 2011;Bastari, Beccacece, Ferretti, Micheli, & Cerrano, 2017;Coll et al, 2014;Damalas et al, 2015;Mavruk, Saygu, Bengil, Alan, & Azzurro, 2018), providing new opportunities to overcome practical and budgetary constraint, especially in poorly studied areas. In this, fishers are a particularly interesting group of stakeholders, as they spend a considerable proportion of their lives in close contact with the marine environment and they become familiar with local species.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, the use of standardized and cost-effective procedures is needed to underpin a large-scale observation strategy that can accommodate countries across a range of baseline knowledge levels and capabilities (Bélisle, Asselin, LeBlanc, & Gauthier, 2018;Latombe et al, 2017). Yet, accessing this expert knowledge (hereafter referred as local ecological knowledge or LEK) is offering new opportunities to Mediterranean research Azzurro, Moschella, & Maynou, 2011;Bastari, Beccacece, Ferretti, Micheli, & Cerrano, 2017;Coll et al, 2014;Damalas et al, 2015;Mavruk, Saygu, Bengil, Alan, & Azzurro, 2018), providing new opportunities to overcome practical and budgetary constraint, especially in poorly studied areas. In this, fishers are a particularly interesting group of stakeholders, as they spend a considerable proportion of their lives in close contact with the marine environment and they become familiar with local species.…”
Section: Introductionmentioning
confidence: 99%
“…These two species showed wide distribution in sandy, muddy or mixed sediments at a wide depth range in sites disturbed and undisturbed (Table I and Figure 3) by fishing activities. From the coast to offshore, benthic assemblages are exposed to a heavy and prolonged history of exploitation, and are subjected to chronic and intensive effects of bottom trawling and fishing, with habitat degradation which in turn homogenised and simplified the benthic assemblages themselves (Bastari et al 2017). In the five sampling periods of this study (from winter 2014 to winter 2016), C. corona was present at low density (5-10 ind.…”
Section: Conclusive Remarksmentioning
confidence: 89%
“…In Pierdomenico et al (2016Pierdomenico et al ( , 2018 documented in the Gioia basin high level of disturbance due to high sedimentation, turbidite flows and intense bottom trawling effort that resulted in scarce environmental status and low abundances of megabenthic communities. It is largely reported that canyons represent very exploited fishing grounds at global level (Ramirez-Llodra et al 2011) and that the bottom trawling is cause of strong alterations of biodiversity and functioning in ecosystems, as in the Blanes and La Fonera canyons (Northwestern Mediterranean Sea), and of negative effects on benthic communities (Pusceddu et al 2014;Bastari et al 2016;Lastras et al 2016;Romano et al 2016). In the northern coast of Sicily, Romano et al (2016) reported significant differences between the macrofaunal assemblages from areas where the fishing activity is forbidden and those where the trawling is permitted.…”
Section: Discussionmentioning
confidence: 99%